Seismic architecture and evolution of the Disko Bay trough-mouth fan, central West Greenland margin. (1st September 2016) - Hofmann, Julia C.; Knutz, Paul C.; Nielsen, Tove; Kuijpers, Antoon
Abstract: The present study is the first to document the large-scale glacigenic evolution of a West Greenland trough-mouth fan (TMF) system, i.e. the Disko Bay TMF, from onset of shelf-based glaciation to present. We have constrained the paleo-ice sheet configuration in the Disko Bay region and determine the controlling factors of ice-stream development using 2D- and 3D-seismic reflection data, seabed bathymetry and stratigraphic information from two exploration wells. This has revealed three stages of the Disko Bay TMF development. The early stage, probably of Pliocene-early Pleistocene age, marks the onset of a central depocentre located below the modern mid-shelf and constructed by sediment progradation delivered through at least two erosive pathways related to fast-flowing, grounded ice. At that time, ice-stream routing in the Disko Bay shelf region was strongly controlled by the pre-glacial topography and structural boundaries associated with fracture zones and deep-seated faults. During the middle evolutionary stage, the focus of deposition shifted from the mid-shelf to two elongate areas fringing the outer margin. The marginal depocentres were not only related to glacial processes but also alongslope deposition by contour currents, which may have developed as a consequence of basin subsidence surrounding the Davis Strait High and the Kangerluk Structure. The late stage of TMF development, presumably representing the late Pleistocene to Holocene, is characterized by the marginal depocentres becoming less significant and sediment aggradation occurring over wide parts of the mid-outer shelf, while features of subglacial erosion are generally absent. In contrast to the inferred fast-flowing ice streams of the early-middle evolutionary stages, this points to the existence of a rather thin and "lightly" grounded ice sheet, i.e. at the threshold of floatation. The "lightly" grounded ice sheet scenario, applying to the late Pleistocene interval of the Disko Bay TMF, was possibly associated with floating ice shelves during periods of maximum cooling, while intermittent and short-lived advances of grounded ice streams may have occurred during interstadial-stadial climate transitions. A controlling factor for the development of the aggradational stage may relate to the prominent basement ridge that separates the Disko Trough from the Egedesminde Dyb depression. We suggest that a neotectonic emergence of the ridge gradually restricted the flow of ice through the central Disko Trough forcing glaciers to diverge along the entire length of the ridge and find complementary drainage routes. Highlights: Three evolutionary stages of the Disko Bay trough-mouth fan (TMF) have been identified. An evolutionary shift between apparent fast ice flow during the early TMF stage and "lightly" grounded ice/floating ice-shelf conditions predominating the late TMF stage has been observed. A controlling factor may have been the neotectonic formation of a basement ridge, located on the inner shelf, providing an impediment to westward glacial drainage of Disko Bay and thus imposing alternative drainage routes.